2017
DOI: 10.1002/ejp.1071
|View full text |Cite
|
Sign up to set email alerts
|

Equimolar mixture of nitroux oxyde and oxygen during post‐operative physiotherapy in patients with cerebral palsy: A randomized, double‐blind, placebo‐controlled study

Abstract: During this randomized placebo-controlled double-blind study, children receiving nitrous oxide and oxygen (N2O) achieved more often the targeted range of motion during physiotherapy sessions after multilevel surgery. Compared to placebo, nitrous oxide and oxygen (N2O) enabled a better management of acute pain related to physiotherapy procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…However, MT is conducted when the patient is conscious. Pain may be a major obstacle to MT sessions in this population [ 31 , 32 ]. Proper pain management and timely ROM acquisition after surgery can not only improve patients’ satisfaction and quality of life but also reduce the burden on nursing staff and the economic burden of the patient group on health and social care services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, MT is conducted when the patient is conscious. Pain may be a major obstacle to MT sessions in this population [ 31 , 32 ]. Proper pain management and timely ROM acquisition after surgery can not only improve patients’ satisfaction and quality of life but also reduce the burden on nursing staff and the economic burden of the patient group on health and social care services.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the mixture of 20% N 2 O and 80% O 2 has an equivalent analgesic effect as well as a good sedative effect with 15 mg morphine [ 37 ]. Notably, it does not combine with hemoglobin and is mainly discharged through the lungs with a strong analgesic effect but a weak anesthetic effect [ 31 , 38 ].…”
Section: Discussionmentioning
confidence: 99%